Changes in smoking prevalence in Russia, 1996–2004. (24th March 2006) - Bobak, M; Gilmore, A; McKee, M; Rose, R; Marmot, M
Abstract : Objectives: In Russia, smoking prevalence has historically been high in men and relatively low in women. Female smoking prevalence is predicted to rise but assessment of changes has been limited by the lack of comparable data. Changes in the prevalence of smoking in Russia between 1996 and 2004, and whether theses changes differed by sociodemographic groups, were investigated. Design: Repeated national interview surveys in 1996 (731 men and 868 women) and 2004 (727 men and 864 women) aged 18 years or more. Main outcome measure: Prevalence of current smoking. Results: The age standardised prevalence of smoking in 1996 and 2004 was 61% and 63%, respectively in men and 15% and 16%, respectively in women (both p values > 0.4). In men, the prevalence of smoking seemed to decline in those with university education (from 51% to 40%, p = 0.085). Among women, smoking appeared to increase in those with university education (from 10% to 17%, p = 0.071) and low levels of self-reported material deprivation (from 11% to 18%, p = 0.053). There was a pronounced increase in prevalence among women living in villages (from 8% to 14%, p = 0.049); the strong urban/rural gradient seen in 1996 became considerably weaker by 2004. Conclusions: Overall smoking prevalence in both men and women in Russia remained stable between 1996 and 2004 but, given the sample size, a moderate increase in female smoking cannot be ruled out. In men, smoking increased among the least educated and declined in the most educated. In women the opposite appeared to occur, in addition to an increase in smoking in rural areas. More long term monitoring of smoking patterns in Russia, especially among women, using sufficiently large surveys, is required.